2010
DOI: 10.1345/aph.1p480
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Hemolytic Anemia Following MF59-Adjuvanted Influenza Vaccine Administration: A Report of Two Cases

Abstract: Influenza vaccination may rarely trigger severe AIHA, shortly after vaccine administration. A mechanism of molecular mimicry is probably involved in the development of these reactions, although the possible role of adjuvants can not be excluded. Patients should be instructed to report signs and symptoms of autoimmune disorders occurring in the first weeks after administration of influenza vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…More recently, authors have reported both positive and negative effects of squalene on the immune system. Whereas Escrich and others (2011) have hypothesized that the chemopreventive effect of extra virgin olive oil on breast cancer may be due at least in part to squalene and phenolic antioxidants, Tritto and others (2009) and Montagnani and others (2011) have attributed an autoimmune reaction of some individuals to a squalene‐based adjuvant used in flu vaccines. Although a mechanism for the possible role of squalene on immunomodulation is not yet at reach, it is apparent that the lipid molecule can in fact influence the immune system most likely by altering the immune cell membrane.…”
Section: Immune System Influencementioning
confidence: 99%
“…More recently, authors have reported both positive and negative effects of squalene on the immune system. Whereas Escrich and others (2011) have hypothesized that the chemopreventive effect of extra virgin olive oil on breast cancer may be due at least in part to squalene and phenolic antioxidants, Tritto and others (2009) and Montagnani and others (2011) have attributed an autoimmune reaction of some individuals to a squalene‐based adjuvant used in flu vaccines. Although a mechanism for the possible role of squalene on immunomodulation is not yet at reach, it is apparent that the lipid molecule can in fact influence the immune system most likely by altering the immune cell membrane.…”
Section: Immune System Influencementioning
confidence: 99%
“…Her anemia improved within two weeks after the administration of steroids and immunoglobulin. (4) Montagnani et al [30] reported the case of a 74-year-old woman with aortic valvulopathy who developed Coombs-positive AIHA approximately three days after the administration of influenza vaccine. She died two days later after being hospitalized despite reduced anemia induced by treatment (corticosteroids and transfusion).…”
Section: Aiha Associated With Viral Infectionsmentioning
confidence: 99%
“…Although the mechanism of pathogenesis of autoimmune disorders induced by the administration of influenza vaccine is unknown, one possibility is the induction of an autoimmune response by molecular mimicry of host antigens by viral-derived peptides that induce crossactivation of autoreactive T or B cells [30]. The etiopathogenesis of autoimmune disorders induced by influenza vaccine remains unclear.…”
Section: Aiha Cases Followed By Administration Of Influenza Vaccinementioning
confidence: 99%
See 2 more Smart Citations